MicroRNA-29 impairs the early phase of reprogramming process by targeting active DNA demethylation enzymes and Wnt signaling - Mariane Fráguas-Eggenschwiler; Reto Eggenschwiler; Jeannine Hoepfner; Josiane Lilian dos Santos Schiavinato; Rodrigo Haddad; Lucila Habib Bourguignon Oliveira; Amélia G. Araújo; Marco A. Zago; Rodrigo Alexandre Panepucci; Tobias Cantz (2016)
Somatic cell reprogramming by transcription factors and other modifiers such as microRNAs has opened broad avenues for the study of developmental processes, cell fate determination, and interplay of molecular mechanisms in signaling pathways. However, many of the mechanisms that drive nuclear reprogramming itself remain yet to be elucidated. Here, we analyzed the role of miR-29 during reprogramming in more detail. Therefore, we evaluated miR-29 expression during reprogramming of fibroblasts transduced with lentiviral OKS and OKSM vectors and we show that addition of c-MYC to the reprogramming factor cocktail decreases miR-29 expression levels. Moreover, we found that transfection of pre-miR-29a strongly decreased OKS-induced formation of GFP+-colonies in MEF-cells from Oct4-eGFP reporter mouse, whereas anti-miR-29a showed the opposite effect. Furthermore, we studied components of two pathways which are important for reprogramming and which involve miR-29 targets: active DNA-demethylation and Wnt-signaling. We show that inhibition of Tet1, Tet2 and Tet3 as well as activation of Wnt-signaling leads to decreased reprogramming efficiency. Moreover, transfection of pre-miR-29 resulted in elevated expression of β-Catenin transcriptional target sFRP2 and increased TCF/LEF-promoter activity. Finally, we report that Gsk3-β is a direct target of miR-29 in MEF-cells. Together, our findings contribute to the understanding of the molecular mechanisms by which miR-29 influences reprogramming.